Penggunaan Job Sheet dalam Pembelajaran Pekerjaan Dasar Teknik Mesin untuk Meningkatkan Hasil Belajar Siswa Kelas X TMP A SMKN 3 Palu - Hidayati Hidayati (Universitas Tadulako, 2021)
Learning basic work in mechanical engineering class X TMP A SMKN 3 Palu shows that student learning outcomes are generally still below the minimum completeness criteria (KKM). This study aimed to determine the increase in student learning outcomes of class X TMP A SMKN 3 Palu by using job sheets in learning basic work techniques. The research subjects were 35 students of class X TMP A SMKN 3 Palu in the 2018/2019 academic year. This research was conducted in 2 cycles and the instruments used were a cognitive test sheet and a practical assessment sheet for psychomotor. Based on the research results obtained in cycle I student learning completeness 71.42% with the number of students who complete learning as many as 25 students. Then completeness of student learning classically increased in cycle II of 94.28% with 33 students who completed learning. Completeness of student learning from cycle I to cycle II has increased by 22.86%. This significant increase indicates that the use of job sheets in learning is quite effective in improving student learning outcomes.